(untitled) (Mustansiria Dental Journal, 2018)
The calcium, inorganic – phosphate of 20 pregnant women with age (20 – 45) years wearing removable partial denture divided into 3 trimester and 10 women married non pregnants as control. In resting saliva the concentration of calcium not changed significantly in pregnant women, and inorganic – phosphorus found not to be changed significantly. The aim of this study was to see the pregnancy related change in human saliva and relation to the oral findings and effect of wearing removable partial denture.